SPIRITUALITAS DOA MENURUT ST AFRAHAT DAN IMPLIKASINYA BAGI KEDEWASAAN JEMAAT - Dani Simarmata (Bethel Press, 2022)
Prayer is a spirituality that is closely related to the Christian life. All age categories are taught the spirituality of prayer. However, this spirituality is starting to be seen as ancient and abandoned by Christians, especially in the postmodern era. Therefore, it is necessary to internalize the spirituality of prayer with different approaches and sources. This study aims to find the meaning of being watchful in prayer according to the church fathers in the book of St Afrahat. The research method used is descriptive qualitative with data collection techniques through library research texts or writings from the Church Fathers that have been written in St Afrahat's book. The results of the study stated that being on guard in prayer is one of the processes so that we do not fall into worldly sins, by being vigilant in prayer is one of the purification of ourselves so as not to be tempted by the worldly.